Rights of a Child to Maintenance Under the Nigerian Legal System - Asonibare, Adelowo Stephen; Wuraola, Oluwabusayo Temitope (NIU Journal of Social Sciences, 2018)
This work examined the right of a child to maintenance under the Nigerian legal system. The significant concern in the rise of matrimonial disputes is made manifest by the enormous and rigorous procedures in dissolving a marriage without adequate concern for the emotional health of the children of the marriage. Most times divorce matters are left lingering in court, appeals upon appeals on interlocutory matters without any concern for the main substance of the subject of dispute. The doctrinal approach is therefore employed by wide consultation of books, articles in journals, articles from the internet by renowned scholars in the area of child’s right to examine the nature of the rights of a child and the extent to which a child can enforce his right to maintenance; particularly in matrimonial causes. It is observed that the position of Matrimonial Causes Act and the Child Rights Act 2003 seems hazy to the effect that a child cannot enforce his right of maintenance before the determination of the matrimonial proceedings, but the child can however lay claim to this right and enforce same under the ambience of the Child Rights Act. It is concluded that the right of a child to maintenance is inalienable, thus can be enforced even before the determination of the proceedings. It is also recommended that awareness, legislative amendments and full institutionalization of the Family Court amongst other things would properly advance the cause of enforcing the rights of a child particularly his right to maintenance even during matrimonial proceedings.